Uniqueness of moving boundary for a heat conduction problem with nonlinear interface conditions - Wei, T. (Elsevier, 2010)
In this paper, based on the maximum principle and the unique continuation theorem, we present a uniqueness result for a moving boundary of a heat problem in a multilayer medium with nonlinear interface conditions.
Keywords: Heat Flux; Multilayer